Environmental education and climate change in a colonial context - Qumsiyeh, Mazin B.; Saeed, Reena; Najajrah, Mohammad; Katbeh-Badr, Nedal; Ikhmais, Hadeel; Simonett, Otto; Mackey, Alex; Libert , Maria E. (Africana Studia, 2022)
Developing and effectively using practical educational modules for adaptation to and mitigation of climate change in locally sensitive ways is critical for sustainability. Such a project was implemented in schools in Palestine in close cooperation and dialogue between academia and an environmental NGO in partnership with national authorities. Panels, posters, power point presentations, and videos (in Arabic and English) were produced via extensive consultation, expert engagements, and focus group meetings. Six field areas region (culturally sensitive, locally relevant) were specifically “packaged” within our region in ways to promote sustainability: Agriculture, Biodiversity, Geography, Energy and Transportation, Climate Change, and Waste and Chemicals. The educational packages were then used and disseminated to educators and students at 14 middle schools in the West Bank initially and shared widely in others schools when they conducted visits to the museum. The educational material were also shared regionally (Jordan, UAE etc.) and globally (including shown at COP25). Climate change material was implemented in the Palestine Institute for Biodiversity and Sustainability in many exhibits and educational modules benefitting thousands even under the difficult conditions of Israeli occupation. Keywords: Behavioral change, Palestine, Middle School Students, museum usage.